PENGARUH LITERASI KEUANGAN, PEMANFAATAN SISTEM INFORMASI AKUNTANSI, PENGGUNAAN TEKNOLOGI INFORMASI, SUMBER DAYA MANUSIA DAN KUALITAS PRODUK TERHADAP KINERJA UMKM DI KEBUMEN - Hanafi, Luthfi Aruna; Kurniawati, Lintang (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of financial literacy, the utilization of accounting information systems, information technology usage, human resources, and product quality on the performance of MSMEs in Kebumen. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 100 MSMEs in Kebumen. The results show that all independent variables have a positive and significant impact on MSME performance. Financial literacy helps MSMEs manage their finances effectively, the use of accounting information systems enhances efficiency and transparency, information technology facilitates operations and marketing, high-quality human resources improve productivity, and good product quality increases customer satisfaction.Keywords: Financial Literacy, Accounting Information Systems, Information Technology, Human Resources, and Product Quality.